Mitochondrial Encephalocardio-Myopathy with Neonatal Hypotonia and TMEM70 Mutation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
The course and metabolic profile of a novel mitochondrial disease with ATPase deficiency and mutation in the TMEM70 gene are described in a retrospective multisite survey of 25 patients (14 boys, 11 girls) from 7 European countries.